Position Paper Number 1 for the Workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“: Instrumental Reason as a Hindering Factor for Meaningful Technology Design - Wolfgang Hofkirchner; Robert M. Bichler (tripleC: Communication, Capitalism & Critique)
This paper is the first of a number of position papers for the workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“